(untitled) (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
This research aims to study the use of artificial intelligence techniques in combating criminal crime as an effective and innovative tool that contributes to enhancing security and protecting society, given the wide and multi-capacity field that this technology provides, such as data analysis, prediction, and other features of artificial intelligence, and to demonstrate the use of its applications in the criminal field. The idea of ​​artificial intelligence technology stems from the development of artificial neural networks that, in the way they work, mimic the human brain. It has the ability to experiment, teach, and self-develop without human intervention. It also provides advanced capabilities for analyzing patterns of criminal behavior, which helps the competent authorities to detect crimes and understand criminal trends. In a more effective way, the study also seeks to discuss the problems facing artificial intelligence technologies and the future problems they raise, especially in light of the accelerating pace of technological development. To achieve the goal of this study, we will adopt the descriptive and analytical approach, in light of the study of the topic “Using artificial intelligence techniques in combating crime ” which we believe is divided into two topics: In (the first) we seek to study: “The nature of artificial intelligence,” while in (the second) we study : “The role of artificial intelligence in combating crime,” and concluded with a summary of the study, including the most important results and recommendations - God willing.